Information on Legal Precedent as an Instrument to Ensure Legal Certainty for Citizens - Arruda Alvim, Eduardo (Revue internationale des Gouvernements Ouverts, 2018)
[extract] The purpose of this brief study is to examine legal precedents as enshrined in the 2015 Brazilian Code of Civil Procedure, in addition to the importance of the principle for ensuring legal certainty for citizens. In fact, transparency in the administration of justice is only possible if the citizen is able to ascertain or have some idea as to the future of a case, in the event he or she opts to resort to the Courts. To investigate this judicial mechanism, let us begin by providing a brief outline of legal precedents and their regulation under the 2015 Brazilian Code of Civil Procedure. We will then turn to an examination of some of the specific modalities of precedent identified.